Penerapan Aplikasi CONCURA pada Sistem Administrasi Kepegawaian di Lembaga Keuangan Syariah - Hermini, Nurlinda; Aza Emiliana, Resta; Marshandi Setiawan, Adrian; Dave Christian, Jonathan; Alpiansah, Restu (Insan Kreasi Media, 2025)
This internship report describes the experiences and knowledge gained during the Community Service Program (KKN) at a financial institution, specifically in the field of human resources administration. The program was designed to provide students with the opportunity to apply academic theories in a real-world professional setting, especially in administrative processes within the Islamic banking sector. The methodology involved a participatory approach, where the author engaged in planning, execution, and evaluation of various administrative tasks such as employee data management, leave and overtime submissions, document sorting, letter registration, and document mobilization using a digital system designed for Human Resource Information Management (HRMIS). The results from KKN, the author not only developed technical skills but also improved soft skills such as communication, teamwork, time management, and problem-solving. The internship allowed the author to understand the importance of accuracy and professionalism in handling administrative work. Overall, this program has broadened the author’s perspective on the dynamics of human resources in a banking environment and has prepared the author to face future challenges in the world of work with confidence and competence.